Boosting Students’ Grammatical Competence through Group Work Activities during Covid-19 Pandemic - Marsevani, Maya (Universitas Pendidikan Ganesha, 2023)
Grammatical skills are components that students, particularly English Education students, must learn and master. Structure and written expression (SWE) of a TOEFL test is one of grammatical skills that students must understand. However, students had difficulties learning SWE on a TOEFL test. Some students struggled to grasp the subject and others were uninterested in mastering SWE. As a result, group work activities were conducted to assist students in improving their grammatical skills. The study employed Classroom Action Research (CAR) on an intermediate grammar class at a private university in Batam. The CAR was implemented in two cycles, with 14 students participating in group work activities for eight meetings. Despite an improvement in the first cycle, it was found that the class remained in the same category before the group work activities were implemented, which was “average.